The impact of Cobalt and Strontium radiation on Pseudomonas aeruginosa - Waleed Jabbar Mhana (Al-Mustansiriyah Journal of Science)
The research aims to study the effect of radiation emitted from different clinical sources, including cobalt and strontium.  The study was carried out using isolates of Pseudomonas bacteria isolated from Baghdad hospitals during the year 2021, about 20 isolates from the blood of patients infected with the bacteria. The results showed a lethal effect on Pseudomonas bacteria when exposed to radiation at different times during one hour, two hours and three hours. Different doses using cobalt with effective 1 mci and 10  mci in the presence and absence of aluminium, and the use of strontium in the presence and absence of aluminium.  Co60 (10Mci) without Alminium, with dose 12.48472106(1hr.), 24.96944212 (2hr.), 37.45416318 (3hr.) that emit Beta and Gamma; Co60 (10Mci) with aluminium with dose 0.023315312×10-7 (1hr.), 0.046630625×10-7 (2hr.), 0.069945936×10-7 (3hr.) that emit Beta ray; Co60 (1Mci) without Alminium with dose 3.4178394 (1hr.), 6.835678887 (2hr.), 10.2535182 (3hr.) that emit Beta and Gamma; Co60 (1Mci) with alminium with dose   0.155992856*10-4 (1hr.), 0.311985712*10-4 (2hr.), 0.467978568×10-4 (3hr.) that emit Beta ray and Sr90 with dose 0.73251×10-2 (1hr.) 1.4650×10-2 (2hr.), 2.19753×10-2 (3hr.)   The results showed that the killing rate of P. aeruginosa bacteria using cobalt 10 mCi without aluminium was 78%, and in the presence of aluminium 100%. In comparison, the killing rate of Pseudomonas bacteria with effective effectiveness of 1 mC without aluminium was 100% and in the presence of aluminium 98%, and the killing rate of Pseudomonas bacteria without aluminium was 83%  and in the presence of aluminium 96% compared with control.